How could patient navigation help promote health equity in sub-Saharan Africa? A qualitative study among public health experts. (March 2021) - Louart, Sarah; Bonnet, Emmanuel; Kadio, Kadidiatou; Ridde, Valéry
The indigents have long been excluded from health policies in sub-Saharan Africa. Despite recent efforts by some countries to allow them free access to health services, they face a multitude of non-financial barriers that prevent them from accessing care. Interventions to address the multiple patient-level barriers to care, such as patient navigation interventions, could help reverse this trend. However, our scoping review showed that no navigation interventions in low-income countries targeted the indigents. The objective of this qualitative study is, therefore, to go beyond the lack of evidence and discuss relevant approaches to act in favor of health care equity. We interviewed 22 public health experts with the objective of finding out which actions related to patient navigation programs (identified in the scoping review for other target groups) could be relevant and/or adapted for the indigents. For each ability to access care described by Levesque and colleagues, we were thus able to list the potential opportunities and challenges of implementing each type of action for the indigents in sub-Saharan Africa. Overall, the experts all felt that patient navigation programs were very relevant to implement for the indigents. They emphasized the need for personalized follow-up and for holistic actions to consider the whole context of the situation of indigence. The recommendations made by the experts are valuable in guiding political decision-making, while leaving room for adaptation of the proposed guidelines according to different contexts.